From Revolutionary Movements to Political Parties
XII, 275 p.
Keywords: This volume is a series of original articles analyzing eleven case studies (from Africa and the Americas) of revolutionary movements that have reconstituted themselves into formal political parties. The book's analyzes the factors influencing the success and failure of these former politico-military movements within their new democratic contexts.